Smart Apps Creator-Based Learning Media Training on Reproductive System Material at Junior High School 3 Labuapi - Johana Aulina Rahmatin; Barinta Nur Respasari; X. Zardht Alex Hidayat; Aris Doyan (Indonesian Journal of Educational Innovation, 2025)
This training activity aims to introduce more effective and interactive learning to students at SMPN 3 Labuapi, West Lombok, in understanding biology concepts, especially in the reproductive system. The activity is carried out through two stages, namely training and mentoring. Training at  Public Junior High School 3 Labuapi introducing learning media based on the Smart Apps Creator application on reproductive system material with interactive content went well. It is hoped that a positive response to the application of this media can increase understanding and motivation in science education. This innovative approach is in line with the need for creative teaching methods in today's world of education.